Dissociable Effects of Monetary, Liquid, and Social Incentives on Motivation and Cognitive Control - Crawford, Jennifer L.; Yee, Debbie M.; Hallenbeck, Haijing W.; Naumann, Ashton; Shapiro, Katherine; Thompson, Renee J.; Braver, Todd S. (Frontiers in Psychology, 2020)
Humans are social creatures and, as such, can be motivated by aspects of social life, like approval from others, to guide decision-making in everyday contexts. Indeed, a common view is that people may have stronger orientation towards social goals or incentives, relative to other incentive modalities, like food or money, however, to date little work has addressed how or if social incentives compare to other types of rewards in motivating goal-directed behavior. The current study tested this claim; across two separate experiments, we compared the effects of two primary incentive types, liquid and social incentives, and their subsequent impact on task performance and self-reported affect and motivation. Critically, the valenced social incentives offered both ecological validity (short video clips-Experiment 1) and continuity with prior stimuli used in the social reward and motivation literature (static images-Experiment 2) when examining their effect on behavior. Across both studies, the results replicate and extend prior work, demonstrating robust effects of liquid incentives on task performance and self-reported affect and motivation, while also supporting an interpretation of weaker motivational and affective effects for social incentives. These patterns of results highlight the complex and wide-ranging effects of social incentives and call into question the effectiveness of social incentives, relative to other incentive modalities, in motivating behavior.